Pemberdayaan Masyarakat Nelayan Melalui Kelompok Mina Mandiri Glayem Di Desa Juntikedokan Kecamatan Juntinyuat Kabupaten Indramayu - Rifa’i, Syaefudin; Natsir, Luthfi Faisal; Kartini, Mulyati (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
The empowerment of fishing communities is an essential effort to improve the welfare of coastal groups that remain socially and economically vulnerable. This study aims to identify the forms of community empowerment carried out through the Mina Mandiri Glayem Fishermen Group in Juntikedokan Village, Juntinyuat District, Indramayu Regency, as well as to analyze the inhibiting factors in its implementation. This research employed a qualitative descriptive approach with data collection techniques including observation, in-depth interviews, and documentation. The findings show that fishermen empowerment has been implemented through institutional strengthening, the provision of fishing facilities such as boats, engines, and fishing gear, training and mentoring by fisheries extension officers, and marketing facilitation through the Glayem Fish Auction Place (TPI). These programs have improved fishermen’s capacities, expanded market access, and fostered collective awareness to cooperate in advancing group interests. However, the implementation of empowerment programs has not been fully optimal due to several obstacles, including limited capital and facilities, dependence on seasons and weather conditions, low human resource capacity, lack of continuous socialization and evaluation, weak inter-agency coordination, and resistance from some fishermen toward group institutions.